Turkish Scorzonera Species Extracts Attenuate Cytokine Secretion via Inhibition of NF-κB Activation, Showing Anti-Inflammatory Effect in Vitro - Bahadır Acikara, Özlem; Hošek, Jan; Babula, Petr; Cvačka, Josef; Budešínský, Miloš; Dračinský, Martin; Saltan İşcan, Gülçin; Kadlecová, Daniela; Ballová, Ludmila; Šmejkal, Karel (Molecules (Basel, Switzerland), 2015)
Scorzonera species are used in different folk medicines to combat many diseases, including the illnesses connected with inflammation. Previous experiments showed anti-inflammatory activity of Scorzonera extracts in vivo. S. latifolia, S. cana var. jacquiniana, S. tomentosa, S. mollis ssp. szowitsii, S. eriophora, S. incisa, S. cinerea, and S. parviflora extracts were, therefore, evaluated for their inhibitory activities of TNF-α and IL-1β production, and NF-κB nuclear translocation in THP-1 macrophages. The HPLC analysis was carried out to elucidate and to compare the composition of these extracts. Major compounds of the tested extracts have been isolated using different chromatographic techniques and further tested for their inhibitory activities on TNF-α and IL-1β production. Several extracts showed promising anti-inflammatory activity in these in vitro tests. Results of HPLC analysis revealed chlorogenic acid as a compound present in all tested extracts. Hyperoside, quercetin-3-O-β-d-glucoside and rutin were also present in varying amount in some Scorzonera species analyzed. Furthermore, eight phenolics which were identified as quercetin-3-O-β-d-glucoside (1), hyperoside (2), hydrangenol-8-O-glucoside (3), swertisin (4), 7-methylisoorientin (5), 4,5-O-dicaffeoyl-quinic acid (6), 3,5-di-O-caffeoyl-quinic acid (7), and chlorogenic acid (8) have been isolated as major phenolic compounds of the tested extracts and, together with eight terpenoids (9-16) previously obtained from different Scorzonera species, have been tested for the inhibition of TNF-α production, unfortunately with no activity comparable with standard.
Keywords: Gene Expression Regulation; Cell Line; Turkey; rostlinné extrakty; anti-inflammatory activity; NF-κB; cytokiny; signální transdukce; techniky in vitro; fenoly; Signal Transduction; TNF-α; Turecko; Plant Extracts; lidé; phenolic; triterpen; Humans; NF-kappa B; regulace genové exprese; makrofágy; buněčné linie; Scorzonera; IL-1β; Cytokines; antiflogistika; Anti-Inflammatory Agents; Phenols; Macrophages; In Vitro Techniques